WhatsApp: Communication between Parents and Kindergarten Teachers in the Digital Era - Aviva , Dan; Simon, Eitan (European Scientific Journal, ESJ, 2021)
The technological revolution has filtered into the field of education and among other things, affects communication between parents and teachers in schools and in kindergartens. A digital method for interpersonal communications enables the immediate transfer of messages to a large number of recipients, which is efficient and ensures transparency of actions and policies. The WhatsApp application is now widely used in correspondence between parents and schools, including in kindergartens. The research investigated how kindergarten teachers in Israel use the social media "WhatsApp" in communication with their parents. Using a quantitative research approach, a specially designed questionnaire was distributed online as a Google.docs document to 161 kindergarten teachers in the North of Israel. The kindergarten teachers reported that they were open to change and willing to adopt new technologies that can help them in their work. However, it appears that the main adoption and use of the WhatsApp tool is for the transmission of information or kindergarten experiences to the parents. The kindergarten teachers felt that the WhatsApp application was advantageous due to its easy accessibility and speed of communication and testified to more sharing and involvement of the parents in the kindergarten activities and work. Nevertheless, several questions led to concerns about the mutual availability of the information that is transmitted, the type of information, and the extent of need for the use of this tool in the present era.